(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Fixed dental prosthesis is becoming more popular for preservation of badly damaged crowns and endodontically treated teeth and also for replacing lost teeth around the world. Complications of fixed dental prosthesis are also becoming very common. Fixed dental prosthesis assures greater retention and stability in addition to comfort. Fixed dental prosthesis is more acceptable to patients when correctly planned and designed which provide predictable function are also enhances the esthetics and psychological well being of the patients. Objective: To assess the complications associated with tooth supported fixed dental prosthesis amongst armed forces personnel reporting to Combined Military Hospital (CMH) Cumilla and Combined Military Hospital (CMH) Dhaka. Materials and Methods: An interview based questionnaire was used for 220 patients followed by clinical oral examination of every individual in this cross sectional study conducted during September 2016 to August 2017 in Combined Military Hospital, Dhaka. Patients soft tissues were checked but the main emphasis was given on recording the information regarding the type of prosthesis being used, material of the prosthesis, location of the prosthesis and the complication present including dental caries, coronal or radicular abutment fracture, root canal treatment failure, periapical lesions, periodontal problems and mechanical failures including occlusal interference, no occlusal contact, decementation of the prosthesis, esthetic problems, porcelain and metal fractures. Periapical radiograph was made to assess mentioned complaints; more so periodontal probing was applied to measure the gingival attachment loss. Results: Approximately 183(83%) patients were using porcelain fused to metal prosthesis with 133(60%) of prosthesis being used in posterior segments of mouth. Complications like dental caries, coronal abutment fracture, radicular abutment fracture, occlusal interferences, root canal failures and decementations were more significantly associated with crowns than bridges (p=0.001). On the other hand esthetic issues, periapical lesions, periodontal problems, porcelain fractures and metal damage were more commonly associated with bridges (p=0.001). All cases of dental caries reported were associated with acrylic crown and bridges, whereas all coronal abutment fractures were associated with metal prosthesis. A significantly higher number of patients who got their fixed dental prosthesis from other sources i.e. paramedics, technicians, dental assistants or unqualified dentists had periapical lesions, decementations, esthetic issues and periodontal diseases. Conclusion: Complications associated with fixed dental prosthesis like root canal failures, decementations, periapical lesions and periodontal disease were more significantly associated with prosthesis fabricated by other sources rather than those acquired from CMHs and private dental care and also in patients using prosthesis for 5 to 10 years. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 75-80